The Identification of Competency-based Human Resource Development Strategy - Bahri, Efri Syamsul; Salsiati (Indo Consultan Energi, 2025)
Human resources are the key to a nation's prosperity. This study aims to describe the strategy for developing human resources based on competency and how to overcome the gap in developing human resources based on competency. This study uses a qualitative method, exploring phenomena related to developing human resources based on competency. Qualitative methods also aim to understand individuals' or groups' meanings, views, or experiences and the context behind the phenomenon being studied. This study also uses a descriptive approach and a literature study. The results of this study indicate that there are eight steps in formulating a strategy for developing human resources based on competency: identification of organizational core competencies, competency gap analysis, human resource development planning, implementation of training and development programs, competency-based performance assessment and evaluation, talent management and succession planning, utilization of technology in competency development, and a culture of continuous learning. Furthermore, the results of this study also obtained eight strategies to overcome the gap in developing human resources based on competency: competency gap analysis, training and development programs, competency-based career development, use of technology and competency management systems, periodic evaluation and feedback, a culture of continuous learning, awards, and incentives, cooperation with educational institutions. The government can use the competency-based human resource development model to realize the Golden Indonesia Generation 2024.